Enzymatic hydrolysis of cellulose (I): relationship between kinetics and physico-chemical parameters - Gama, F. M. (1997)
Several purified celluloses (Avicel PH 101; Sigmacell Type 100; Whatman CF-11; Cotton; Amorphous cotton) were physically characterised. The crystallinity, particle size and degree of polymerisation were analysed during successive enzymatic digestions with a commercial cellulase of Trichoderma reesei under conditions of high enzyme to substrate ratio. The variation in the degree of polymerisation after 30 min of enzymatic digestion, was measured by the variation of the reducing power of the insoluble fibres, correlated with the cellulose solubilised after 12h. The results obtained suggest that the overall kinetics of digestion are governed by the amorphous area of the fibres which is accessible to endoglucanases. The effect of the substrate and enzyme concentrations on the initial kinetics of hydrolysis was also studied. The relative susceptibility of the different substrates to enzymes depended on the enzyme to substrate ratio, owing to the different adsorption properties of the tested celluloses. Analysis of the effect of the physical properties of the substrate cannot therefore be done neglecting the enzyme to substrate ratio.